Spatial effects in the bid price setting strategies of the wholesale electricity markets: The case of Colombia (2017)
Weather conditions in Colombia vary greatly throughout the territory and therefore the location of electricity generating plants plays a key role in their bid pricing strategies. To account for these location-specific pricing strategies this paper estimates a Spatial Durbin Model (SDM) with monthly data gathered from the 17th largest hydraulic electricity generating plants of Colombia on bid prices, generation, energy inputs and positive reconciliation over the period January 2005-August 2015 and controlling also for the system marginal prices and the economy cycle. The paper reports three main results. First, firms ́ bid prices are negatively affected by the energy inputs of the rivals, second they are unaffected by positive reconciliation payments to the rivals and third they are negatively affected by the generation amounts of the rivals. One potential policy recommendation of these results is the need to implement balancing markets to signal more efficiently the pricing strategies in these markets.